Quality management and safety performance: the influence of ethical leaders among public sector employees - Birasnav, M.; Dahiya, Rinki; Dalpati, Avadhesh (The TQM Journal, 2026)
Keywords: Ethical leadership; Incentive; Job satisfaction; Motivation for QM implementation; Perceived safety performance; Public sector; Quality (philosophy); Structural equation modeling; Survey data collection; Test (biology); Work (physics); dept.mgt

Do schools have hindrance of quality to promote innovativeness? Examining the role of empowering leadership and stakeholder involvement - Birasnav, M.; Dahiya, Rinki; Bharti, Teena (International Journal of Quality & Reliability Management, 2024)
Purpose Schools provide high priorities to offer innovative curricular and cocurricular programs, and leaders make necessary efforts to promote enablers and overcome disablers for sustaining their innovativeness. With the background of quality management and stakeholder theories, the present study examines the interplay of hindrances to quality between empowering leadership, stakeholder involvement and organizational innovativeness. Design/methodology/approach Responses of 157 American school principals collected through the Teaching and Learning International Survey 2018 by the Organization for Economic Cooperation and Development were used and analyzed to test the proposed hypotheses. Findings Results show that empowering leadership behaviors of school principals support promoting organizational innovativeness, and involvement of stakeholders with the school activities also promotes organizational innovativeness. Interestingly, when American schools faced a high level of hindrance to providing quality education to their students, principals’ high level of empowering leadership behaviors promoted organizational innovativeness. Originality/value This is the first time in the literature that the interplay between empowering leadership, stakeholder involvement and hindrance of quality education has been examined to promote organizational innovativeness.
Keywords: Empowering leadership; Hindrance of quality education; Organizational innovativeness; Quality management; Stakeholder involvement; dept.mgt; peer-reviewed

Improving school performance and student academic orientation: the role of safety-oriented knowledge management and diversity - Birasnav, M.; Gantasala, Prabhakar Venugopal; Gantasala, Swapna Bhargavi (VINE Journal of Information and Knowledge Management Systems, 2021)
Purpose The purpose of this study is to examine the influence of the implementation of safety-oriented knowledge management (KM) processes and student diversity acceptance in schools and the interaction effect of safety-oriented KM processes and student diversity acceptance over school performance and student academic orientation. Design/methodology/approach Responses of 977 American schools available in the database of the National Center for Education Statistics were analyzed using hierarchical regression analyses. Findings Results show that implementation of safety-oriented KM processes and diversity acceptance in schools have varying effects on school performance and student academic orientation. The impact of knowledge acquisition from parents on the academic achievement of students is positive and stronger in schools that are low in student diversity acceptance than schools that are high in student diversity acceptance. Originality/value This study adds value to the KM literature by exploring how KM processes are executed in American schools to improve their performance and students’ academic orientation and how diversity among students alters the strength of the relationships.
Keywords: Diversity acceptance; Knowledge management processes; School performance; School safety; Student academic orientation; dept.mgt; peer-reviewed

How Do Firms Build Green Supply Chain Learning System? A Theoretical Framework and Directions - Birasnav, M.; Han, Seungmin; Arora, Ridhi; Sangar, Ruby (Corporate Social Responsibility and Environmental Management, 2026)
Keywords: Green innovation; Mechanism (biology); Perspective (graphical); Resource (disambiguation); Supply chain; Supply chain management; Workforce; corporate social responsibility; dept.mgt; environmental performance; exploitation; exploration; green supply chain; leadership; learning system

Performance evaluation of geospatially assisted reference evapotranspiration models - Pandi, Dinagarapandi; Saravanan, Kothadaramanan; Kuppusamy, Mohan; Birasnav, M. (Arabian Journal of Geosciences, 2022)
Mapping of spatiotemporal distribution of evapotranspiration becomes important for sustainable water management as water scarcity is nowadays a growing concern in almost all the continents. In general, researchers estimate evapotranspiration by multiplying the computed reference evapotranspiration (ETo) with the corresponding crop coefficient. Such estimation of ETo requires data related to spatiotemporal meteorological and vegetation field characteristics, and however, these data are rarely available in most developing countries such as India. Thus, researchers constantly develop various methods and evaluate the applicability of these methods to accurately capture spatiotemporal distribution. The purposes of this study are to (a) examine the applicability of Hargreaves and MODIS ETo method to map the spatiotemporal distribution over Thamirabarani basin located in Southern India and (b) evaluate the performances of Hargreaves and MODIS ETo methods and compare it to FAO 56 Penman–Monteith method. To achieve these purposes, ETo data of Hargreaves method and MODIS ETo method over Cheranmadevi meteorological observatory are extracted and performances of these methods are compared with FAO 56 Penman–Monteith method. Results show that a match exists among all the three ETo datasets, and no major deviations have been observed. However, this study suggests local calibration of Hargreaves and MODIS ETo method as considerable mismatch has been observed at ETo daily value. Overall, the conclusion of this study encourages the application of the Hargreaves method and MODIS ETo method in developing countries, where the data shortage condition prevails.
Keywords: Evapotranspiration; FAO 56 Penman–Monteith method; Hargreaves method; MODIS ETo; Thamirabarani basin; dept.mgt; peer-reviewed

Routing vehicles through cross-docking facility for third party logistics service providers - Birasnav, M.; Kalaivanan, S.; Ramesh, A.; Tibrewala, Rajendra (International Journal of Operational Research, 2020)
This study focuses on a specialised vehicle routing problem (VRP) to transport matchboxes from manufacturing companies to retailers through a cross-dock (cross-docking facility) operated by a third party logistics service provider. Three processes (unloading, consolidating, and loading) are carried out at a cross-dock for completely avoiding or keeping inventory for a very short time. The specialised VRP, addressed in this paper, consists of multiple suppliers (each supplier can produce different brands of products for any number of customers) and multiple customers (each customer can receive orders from any number of suppliers). A mixed integer linear programming model has been developed to solve this kind of NP-hard problem. The objective of this model is to minimise total cost incurred in picking up and transporting the matchboxes from the manufacturers to cross-dock, consolidating matchboxes at cross-dock, and in transporting and delivering the matchboxes to the customers. This study also proposes an effective heuristic procedure to solve the same problem and compares the solution obtained using the heuristic procedure to the optimal solution obtained using the exact method. The findings show that the heuristic method, proposed by us, generates near optimum solutions using significantly less computational time than the exact method.
Keywords: NP-hard; consolidating; cross-docking; dept.mgt; heuristic; logistics service provider; multiple customers; multiple suppliers; peer-reviewed; vehicle routing

Total quality leadership and organizational innovativeness: the role of social capital development in American schools - Birasnav, M.; Gantasala, Swapna Bhargavi; Gantasala, Venugopal Prabhakar; Singh, Abhishek (Benchmarking: An International Journal, 2022)
Purpose The purpose of this study is to explore the relationship between total quality leadership, social capital development and organizational innovativeness in the school environment. While there are research studies focused on the impact of leadership on implementing quality management practices, innovation and organizational performance, the mediating effect of social capital development has not been explored on the influence of the school leaders. Design/methodology/approach To achieve the purpose of this study, data collected from 158 principals, who participated in the Teaching and Learning International Survey 2018, were analyzed using structural equation modeling. Findings This study found that total quality learning-oriented school leaders are supportive of developing social capital in their schools, and such social capital development is very useful to improve organizational innovativeness. Interestingly, social capital development has been found to mediate the relationship between total quality learning-oriented school leadership and organizational innovativeness. Practical implications This study submits evidence for two major activities that school leaders perform: learning- and control-oriented activities, both being important for improving and measuring quality in the educational sector. This study clearly shows that control-oriented activities lean toward negatively on social capital while learning-oriented activities strongly and positively influence social capital development. From this study, practitioners can be aware and consciously promote social capital development in schools and that social capital development mediates the influence of total quality leadership and innovation in schools. Originality/value Schools can be visualized as guarded communities for creating a secure environment for students in support of learning. This research study shows that the combined cognitive capital, structural capital and relational capital mediate the impacts of total quality leadership on innovativeness in schools. Thus, school leaders should first establish a mechanism to develop social capital among their employees to bring up innovative initiatives.
Keywords: Organizational innovativeness; School leaders; Social capital; TALIS; Total quality leadership; dept.mgt; peer-reviewed

Green supply chain management: A theoretical framework and research directions - Birasnav, M.; Chaudhary, Richa; Henry Dunne, James; Bienstock, Joshua; Seaman, Cristina (Computers & Industrial Engineering, 2022)
Practitioners and academicians dedicate significant attention to tackling initiatives and executing mechanisms to address society’s environmental concerns. Further, organizations and researchers recognize that there is a need to implement green supply chain management (GSCM) practices as a part of green strategy. To date, embedding a sustainability dimension into supply chain management remains a challenge for organizations given the lack of systematic knowledge of the key dimensions of GSCM practices, the factors that influence the implementation of GSCM practices, and the benefits that organizations gain through the implementation of such practices. To address this problem, this study reviews 151 research articles published between 1997 and 2021 in the GSCM literature, and offers a theoretical framework that synthesizes and integrates the knowledge acquired from the reviewed literature. This framework includes various dimensions of GSCM practices identified in the past research studies, the antecedents that influence implementation of GSCM practices, and the outcomes of implementation of such practices. Further, this study offers theoretical and practical perspectives to support future research utilizing a research model as a baseline to guide organizations in the understanding of the primary GSCM attributes, their predictors, and benefits.
Keywords: Antecedents; Green supply chain; Outcomes; Systematic literature review; dept.mgt; peer-reviewed